(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Urbanization is closely linked to modernization, industrialization, and the sociological process of rationalization. Urbanization is not merely a modern phenomenon, but a rapid and historic transformation of human social roots on a global scale, whereby predominantly rural culture is being rapidly replaced by predominantly urban culture. Urbanization occurs as individual, commercial, and governmental efforts reduce time and expense in commuting and improve opportunities for jobs, education, housing, and transportation. Many rural inhabitants come to the city for reasons of seeking fortunes and social mobility. But the picture of urbanization is not so much glorious as it apparently seems. Modern cities have grown in a haphazard and unplanned manner due to fast industrialization. Cities in developing countries become over-populated and over-crowded partly as a result of the increase in population over the decades and partly as a result of migration.